PREVALENCE OF GESTATIONAL DIABETES AND SOME RELATED FACTORS AT QUANG NINH PROVINCIAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of gestational diabetes mellitus and its associated factors based on univariate analysis among pregnant women at Quang Ninh Provincial General Hospital in 2025. Subjects and Methods: A cross-sectional study was conducted on 334 pregnant women attending reproductive healthcare services at the Endocrinology Clinic, Department of General Internal Medicine, Quang Ninh Provincial General Hospital. Participants were selected using a convenience sampling method. Results: The prevalence of gestational diabetes mellitus was 39.8%. The mean age of affected women was 28.2 ± 4.56 years, with the majority aged 25–34 years (64.7%). On univariate analysis, a history of macrosomia was associated with gestational diabetes mellitus; however, the number of cases was small (n = 7), and the result should be interpreted with caution. In addition, factors such as maternal age ≥ 35 years, history of miscarriage/stillbirth, family history of diabetes, and the presence of hypertension or dyslipidemia were also associated with gestational diabetes mellitus on univariate analysis.
Keywords: gestational diabetes mellitus; prevalence; associated factors; pregnancy.